Rekayasa Struktur Bangunan Tahan Gempa dengan Material Komposit Ramah Lingkungan - Kiki Riskianti Nanda; Winda Dwi Puspita (CV. Aksara Global Akademia, 2024)
Indonesia is a country with a high level of earthquake vulnerability, thus demanding innovation in building structural engineering that is not only safe but also environmentally friendly. In the context of sustainable development, bamboo as an abundant local material is starting to gain attention as an alternative to conventional materials. Bamboo, when processed into composites in the form of fibers or in combination with thermoplastic and thermoset polymers, has been proven to have superior mechanical properties, including tensile strength, stiffness, and resistance to chemical degradation. In addition, the characteristics of water absorption that are controlled through certain treatments make bamboo composites more competitive compared to synthetic materials. The application of bamboo composites in construction is not only limited to new materials in structural elements, but also effective in retrofitting methods. For example, recent research shows the potential of bamboo composites in strengthening reinforced concrete beams and improving the performance of frame systems in earthquake-resistant structures. In line with this, seismic design regulations and standards such as the comparison between SNI 1726:2012 and SNI 1726:2019 demonstrate the importance of adapting structural designs to local seismic conditions. The integration of bamboo composite materials with structural capacity analysis, numerical simulation, and pushover analysis methods has yielded promising results for improving building resilience to dynamic loads. Beyond technical aspects, this approach also supports environmental objectives. Several studies have even developed eco-friendly home prototypes utilizing innovative material combinations, including geopolymer blocks and natural fibers. Thus, the use of bamboo composites not only provides a technical solution to earthquake challenges but also contributes to global efforts to reduce the carbon footprint of the construction sector.